2008
DOI: 10.1021/jp8074145
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Enhanced Raman Scattering for Molecules Adsorbed on TiO2 Nanoparticles: Charge-Transfer Contribution

Abstract: Surface-enhanced Raman scattering from molecules adsorbed on TiO 2 nanoparticles has been observed. This is attributed to the dominant contribution of the TiO 2 -to-molecule charge-transfer mechanism. The chargetransfer process is largely dependent on the intrinsic nature of the adsorbed molecules and the surface properties of the semiconductor. Both the stronger electron attracting ability of groups para-to the mercapto group bonded with TiO 2 surface and the plentiful surface states of TiO 2 nanoparticles ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
304
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(338 citation statements)
references
References 27 publications
25
304
0
3
Order By: Relevance
“…Since R6G is a widely used Raman probe, a deeper understanding of the interaction of R6G and graphene gives us the opportunity to collect more reliable signals when using SERS on a flat graphene surface [27], which is a method that promises to provide cleaner and more reproducible Raman signals. Direct measurement of the Raman enhancement factor can be applied to a larger class of GERS and other chemical mechanismdominant Raman enhancement situations [28,29], which may involve high fluorescence quantum yield dyes. Direct measurement of the Raman enhancement factor will also provide us with more capabilities to further explore the GERS effect and the graphenecovered SERS substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Since R6G is a widely used Raman probe, a deeper understanding of the interaction of R6G and graphene gives us the opportunity to collect more reliable signals when using SERS on a flat graphene surface [27], which is a method that promises to provide cleaner and more reproducible Raman signals. Direct measurement of the Raman enhancement factor can be applied to a larger class of GERS and other chemical mechanismdominant Raman enhancement situations [28,29], which may involve high fluorescence quantum yield dyes. Direct measurement of the Raman enhancement factor will also provide us with more capabilities to further explore the GERS effect and the graphenecovered SERS substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The Becke-Perdew (BP86) XC-potential [91,92] and a triple-polarized slater type (TZP) basis set from the ADF basis set library were used in our simulation. The validity of using DFT and ADF for quantum mechanical SERS calculation has already been proven by many researchers [37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Computational Approach and Detailsmentioning
confidence: 98%
“…However, recent theoretical [37] as well as experimental [38,39] studies has shown that under certain conditions the CT enhancement can be much larger than is usually predicted earlier. In addition, large SERS enhancements have also been observed for molecules interacting with small nanoclusters or nanocrystalline semiconductor surfaces, both of which are not expected to support plasmon resonances and thus should show only small EM enhancement [40][41][42].…”
mentioning
confidence: 99%
“…One possible explanation is that the mechanism is related to a charge transfer (CT) from the semiconductor to the analyte. 32,33 In the case of TiO2 nanoparticles the specific surface area and the surface defects have been considered to affect the intensity of the Raman scattering. 33 In addition to the CT mechanism the optical properties of multi-layered thin-film structures should be noted.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…32,33 In the case of TiO2 nanoparticles the specific surface area and the surface defects have been considered to affect the intensity of the Raman scattering. 33 In addition to the CT mechanism the optical properties of multi-layered thin-film structures should be noted. Alessandri et al 17 studied ALD-TiO2 coatings on SiO2 nano-spheres with the conclusion that the refraction index contrast between the particle and the coating may allow total reflection of the light inside the TiO2 core shell and thus enable the enhancing effect in Raman signal by stacking the particles.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%